Pericardial Solitary Fibrous Tumor on FDG PET/CT. (January 2019) - Shao, Dan; Wang, Shu-Xia
Abstract : Abstract: Solitary fibrous tumor, which can occur in all parts of the body and is more frequently found in the visceral pleura, is a rare mesenchymal tissue-originating spindle cell tumor derived from CD34-positive dendriticmesenchymal cells, but it rarely occurs in the pericardium. We reported the FDG PET/CT findings of a pathologically confirmed benign pericardial solitary fibrous tumor in a 51-year-old woman.